Salvage treatment for relapsed/refractory Hodgkin lymphoma: role of allografting, brentuximab vedotin and newer agents. (3rd March 2016) - Martino, Massimo; Festuccia, Moreno; Fedele, Roberta; Console, Giuseppe; Cimminiello, Michele; Gavarotti, Paolo; Bruno, Benedetto
ABSTRACT: Introduction : Second-line, salvage chemotherapy followed by high-dose chemotherapy and autologous stem cell transplantation (AUTO-SCT) is the standard of care for patients with relapsed/refractory (R/R) Hodgkin lymphoma (HL). Approximately 50% of patients relapse after AUTO-SCT and their prognosis is generally poor. Brentuximab Vedotin (BV) has demonstrated efficacy in this setting and allogeneic (ALLO)-SCT represents an option with curative potential in this subgroup of patients. Areas covered : A systematic review has been conducted to explore the actual knowledge on ALLO-SCT, BV and newer agents in R/R HL. Expert opinion : The introduction of BV in clinical practice has significantly improved the management of post-AUTO-SCT relapses and the drug can induce durable remissions in a subset of R/R HL. Allografting select patients has been used to improve clinical outcomes and recent case series have begun to explore BV as a potential 'bridge' to allo-SCT, even though the optimal timing of ALLO-SCT after BV response remains undetermined. However, reduced tumor burden at the time of ALLO-SCT is a key factor to decrease relapse risk. Based on the unique composition of the tumor, more recently new agents such as PD-1 inhibitors have been developed. The potential role of PD-1 inhibitors with ALLO-SCT remains to be explored.